Simulations of edge localised mode instabilities in MAST-U Super-X tokamak plasmas. (8th May 2020) - Smith, S.F.; Pamela, S.J.P.; Fil, A.; Hölzl, M.; Huijsmans, G.T.A.; Kirk, A.; Moulton, D.; Myatra, O.; Thornton, A.J.; Wilson, H.R.
Abstract: The high heat fluxes to the divertor during edge localised mode (ELM) instabilities have to be reduced for a sustainable future tokamak reactor. A solution to reduce the heat fluxes could be the Super-X divertor, which will be tested on MAST-U. ELM simulations for MAST-U Super-X tokamak plasmas have been obtained, using JOREK. A factor 10 decrease in the peak heat flux to the outer target and almost a factor 8 decrease in the ELM energy fluence when comparing the Super-X to a conventional divertor configuration has been found. A detached MAST-U case, after the roll-over in the target parallel electron density flux, is used as a starting point for ELM burn-through simulations. The plasma burns through the neutrals front during the ELM causing the divertor plasma to re-attach. After the crash a transition back to detachment is indicated, where the recovery to pre-ELM divertor conditions occurs in a few milliseconds, when the neutral pressure is high in the divertor. Recovery times are shorter than the inter-ELM phase in previous MAST experiments. The peak ELM energy fluence obtained after the ELM burn-through is 0.82 kJ/m 2, which is significantly lower than that predicted from the empirical scaling of the ELM energy fluence - indicating promising results for future MAST-U operations.